Modelagem e comparação da potência elétrica e do coeficiente de potência de turbinas magnus segundo o comportamento dos perfis cilíndricos - Olivera, Luis Enrique Manga (2017)
This thesis presents the model of Magnus turbines based on the forces produced by the cylindrical airfoils, resulting in the curves of net mechanical power and power coefficient, besides demonstrating the effects of the coupling an induction machine in the set turbine-generator. The lift and drag forces are obtained through simulations of computational fluid dynamics, are simulated seven different cylinder types. With these forces were determined the drag and lift coefficients respectively for each of the profiles, and they were observed three profiles that take better advantages of these forces. Then, wind turbine models are developed for each profile obtaining the mechanical power curves, presenting in this thesis the model of one profile. In addition, they are also obtained the power coefficient curves as a function of the tip speed ratio (TSR) and the cylinder speed ratio (CSR). Next, were compared the power curves for a wind speed of 7 m/s of the three profiles mentioned above. Finally, a squirrel cage machine is coupled to the Magnus turbine to determine the electrical power generated by the generator and the electrical power losses, resulting in the electrical power of the wind turbine in relation to the turbine angular velocity and the cylinder angular velocity. Obtaining results of net mechanical power, for wind speeds of 7 m/s, close to 16 kW and of electric power supplied around 14 kW. Regarding the power coefficient of the developed model, is obtained a value of 0.359 for a TSR of 1.4. In this thesis we detail the methodology used to model different types of Magnus turbine, as well as the basic concepts to implement techniques of MPPT control with the main parameters of this type of wind turbine.